2011
DOI: 10.1111/j.1600-0501.2010.02100.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vitro biocompatibility of NanoBone® and BioOss® for human osteoblasts

Abstract: Both scaffolds caused only little damage to human osteoblasts and justify their clinical application. However, NanoBone(®) was able to support and promote proliferation of human osteoblasts slightly better than BioOss(®) in our chosen test set-up. The results may guide doctors and patients when being challenged with the choice between a natural or a synthetic biomaterial. Further experiments are necessary to determine the comparison of biocompatibility in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
26
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 9 publications
4
26
0
1
Order By: Relevance
“…This is in agreement with the previously published literature where it has been shown that human osteosarcoma cell lines, osteoblasts [16], bone marrow derived mesenchymal stem cells [32], and human tooth germ cells [33] are able to adhere and grow on MTA and similarly osteoblasts [34], mesenchymal stem cells from peripheral blood [35], or mesenchymal stem cells from bone marrow [36] can grow on Bio-Oss. Moreover, in the present study, we were able to directly compare the three materials and demonstrate for the first time that dental stem cells seemed to prefer dentin chips and MTA as opposed to Bio-Oss.…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with the previously published literature where it has been shown that human osteosarcoma cell lines, osteoblasts [16], bone marrow derived mesenchymal stem cells [32], and human tooth germ cells [33] are able to adhere and grow on MTA and similarly osteoblasts [34], mesenchymal stem cells from peripheral blood [35], or mesenchymal stem cells from bone marrow [36] can grow on Bio-Oss. Moreover, in the present study, we were able to directly compare the three materials and demonstrate for the first time that dental stem cells seemed to prefer dentin chips and MTA as opposed to Bio-Oss.…”
Section: Discussionsupporting
confidence: 92%
“…Unlikely to our study, where no difference in the cell number between materials was found in the study by Warnke et al significantly lower number of cells in the presence of Bio Oss was recorded. Furthermore, comparing the adhesion and quantity of human osteoblasts cultured on “golden standard” Bio Oss and synthetic bone substitute—Nano Bone for 7 days, more cells with cytoplasmic extensions were observed in the presence of Nano Bone . Hence, there are many scaffolds including the ones used in our study which exhibit good biocompatibility and could replace materials currently used in tissue engineering.…”
Section: Discussionmentioning
confidence: 83%
“…Based on the findings of others, NHA1 supported and promoted proliferation of human osteoblasts slightly better than DBBM (Liu et al. ). Ghanaati et al.…”
Section: Discussionmentioning
confidence: 90%